Crisis and the Refounding of the Democratic Myth: The Chilean October, Questions and Tensions [Crisis y Refundación del Mito Democrático: El Octubre Chileno, Preguntas y Tensiones] - Arancibia-Carrizo, J (Universidad De Valparaíso, Chile, 2021)
Based on a critical theoretical tradition of democracy, the article rehearses an interpretation of the Chilean revolt of October 2019. It is argued that this episode indicates the exhaustion of the myth in which democracy obtains its legitimacy and perpetuation as a promise of the realisation of its founding values. To this end, it examines the overall historical context in which the Chilean democratic transition is taking place, thus discovering its close link to the order designed by the Chilean dictatorship. A series of symbolisms articulate the global market order with the social model favoured by the dictatorship, but implemented with a democratic appearance. Finally, the elements that allow us to understand the signs of the collapse of the democratic mythologem in the October revolt are reviewed and questions are asked about the political challenges that are posed. © 2021 University of Valparaiso. All rights reserved.